SOCIO-CULTURAL-BASED PAI LEARNING STRATEGIES IN FORMING ATTITUDES OF RELIGIOUS TOLERANCE AND MODERATION AT SMPN 1 PRIGEN - Huda, Ahmad; Wahidmurni, Wahidmurni; Jazariyah, Ita; Aminatuz Zuhriyah, Indah (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study is grounded in the importance of promoting tolerance and religious moderation values within Indonesia's pluralistic society. Islamic Religious Education (PAI) and Character Education are expected not only to deliver cognitive understanding but also to shape inclusive and respectful student character. The aim of this study is to examine socio-cultural-based instructional strategies in shaping students' tolerance and religious moderation at SMPN 1 Prigen. This research employed a qualitative approach with a case study design, involving PAI teachers, school principals, students, and vice principals as informants. Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that teachers implemented contextual, participatory, reflective, and culturally grounded strategies. Lessons were connected to students' daily lives, encouraging critical discussions, personal reflections, and collaborative social activities. The learning process was also supported by the Pancasila Student Profile Strengthening Project (P5) and the role modeling of moderate behavior by teachers. In conclusion, the socio-cultural-based teaching strategies effectively fostered students' tolerance and religious moderation and are highly relevant to multicultural education settings in Indonesia.